Pengaruh Aplikasi Pseudomonas fluorescens dan Trichoderma spp. terhadap Penyakit Akar Gada serta Pertumbuhan Tanaman Kubis (Brassica oleracea L.) di Desa Candikuning, Tabanan, Bali - PRADNYANA, I KADEK NGESTIKA; SUNITI, NI WAYAN; SUADA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
The effect of Pseudomonas fluorescens and Trichoderma spp. Applications against Clubroot Disease and Growth of Cabbage (Brassica oleracea L.) in Candikuning Village, Tabanan, Bali The research was aimed to find the effectiveness of P. fluorescens and Trichoderma spp. in suppressing clubroot disease caused by P. brassicae Wor. and increasing the growth of cabbage plants as well. The microbes treatments were set on randomized block design, consisting of 36 treatments and 3 replications. The variables observed were percentage of attack, number of clubroot, microbial density, plant height, leaf area, chlorophyll contents, and plant weight,. The results showed that the combination of P. fluorescens and Trichoderma spp. was able to suppress the percentage of pathogen attack and increase the growth of cabbage plants as well. The most effective treatment was combination between P. fluorescens-1 and Trichoderma-4, followed by combination treatment of P. fluorescens-1 and Trichoderma-3 and then P. fluorescens-1 and Trichoderma-5.